2021
DOI: 10.1093/pm/pnab073
|View full text |Cite
|
Sign up to set email alerts
|

Is Thought Management a Resource for Functioning in Women with Fibromyalgia Irrespective of Pain Levels?

Abstract: Objective This study aimed to examine the relationship between cognitive factors (cognitive fusion and catastrophizing) and functional limitation experienced by fibromyalgia patients across different levels of pain severity (i.e. moderation). Methods The sample comprised 226 women with fibromyalgia. Their mean age was 56.91 years (SD = 8.94; range = 30 to 78 years). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Research has repeatedly shown that pain catastrophizing and pain acceptance are important predictors of self-reported physical functioning in samples with acute [ 104 , 105 ] and chronic pain [ 105 , 106 ], including FM [ 41 , 107 , 108 , 109 , 110 ]. Our findings are consistent with the previous evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Research has repeatedly shown that pain catastrophizing and pain acceptance are important predictors of self-reported physical functioning in samples with acute [ 104 , 105 ] and chronic pain [ 105 , 106 ], including FM [ 41 , 107 , 108 , 109 , 110 ]. Our findings are consistent with the previous evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on previous research [10,21,22], where the impact of pain catastrophization on the perception of pain severity has been demonstrated, it could be hypothesized that pain avoidance could mediate the relationship between pain severity and self-efficacy, taking into account the moderating effect of pain catastrophizing on the relationship between pain severity and pain avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, our goal has been to test whether adherence to walking is an important contextual factor to be considered in the relationship between pain catastrophizing and fatigue. Based on previous studies [ 28 , 41 ], it would be expected that, in the worst-case scenario, that is to say when the contextual variables are especially limiting (i.e., when patients do not walk at all), individual status (i.e., fatigue) will be so unfavorable that there will be little room for pain catastrophizing to contribute to it. In contrast, when patients adhere to walking, we expect fatigue to be high if they walk while using biased interpretation (i.e., catastrophizing).…”
Section: Introductionmentioning
confidence: 99%